The art of the bribe : corruption under Stalin, 1943-1953 - Heinzen, James W. (Yale-Hoover series on authoritarian regimes., 2016)
The first archive-based study of official corruption under Stalin and a compelling new look at the textures of everyday Soviet life after World War II In the Soviet Union, bribery was a skill with its own practices and culture. James Heinzen's innovative and compelling study examines corruption under Stalin's dictatorship in the wake of World War II, focusing on bribery as an enduring and important presence in many areas of Soviet life. Based on extensive research in recently declassified Soviet archives, The Art of the Bribe offers revealing insights into the Soviet state, its system of law and repression, and everyday life during the years of postwar Stalinism.